Factors influencing fast food consumption: a case study of University of Venda Students, Limpopo, South Africa - Rabotata, S.; Malatji, T. L. (Technium Social Sciences Journal, 2021)
Eating fast foods more than twice per week is associated with more weight gain and insulin resistance in otherwise healthy young adults. However many consumers see fast foods as symbols of wealth, progress and well-ordered openness of western society. Studies reveal that fast food consumption is the dominant dietary pattern among children and young adults today. However there is little data on the factors influencing fast food consumption in South Africa. Therefore this research paper focuses on factors influencing fast food consumption in South Africa. This is an empirical data which was obtained using exploratory and descriptive research design. Data was collected through unstructured interview of focus groups. The interview involved a direct interaction between the researcher and a group. Participants reported to use fast foods due to the perceived lack of time to prepare one’s own meal. Fast food consumption was found to be more frequent among participants especially during lunch times. The following findings were recorded as factors influencing fast food: Lack of time, change in living conditions, lack of cooking skills & cooking utensils, fun & cravings, socializing and convenience.